The Development of Probing Prompting-Based Module on Calculus 2 Course for Mathematics Education Study Program - Asmaul Husna; Nailul Himmi (Mathematics Research and Education Journal, 2018)
This study aimed at developing the teaching materials in the form of probing prompting-based module on Calculus2 as well as revealing its quality. This research usedthe procedural development model of Instructional Development Institute (IDI) consisting of three stages, namely define, development and evaluation. The development procedure design involved front-end analysis, prototype, and assessment phase. The product assessment was trough descriptive design. Two validators performed the product assessment, they werethe lecturers of mathematics education forCalculus 2course andthe learning media lecturers. The research object was the quality of teaching materials based on the established criteria. The data were the preparation and development process ofthe teaching materials as well as the quality of developed materials. The research instrument was a validation sheet in the form of checklist about the quality of the teaching materials. The product quality data were descriptive and convertedinto scores of 1, 2, 3 and 4 for the criteria of “very bad”, “bad”, “good”, and “very good”. The developed material was in the form of calculus 2module coveringfour subjects. The result of the material validator assessment wasin the percentage of 83.33% that can be catagorized as “good” and from the media validator was 94.44% with “very good” category. It means that the developed material has met the established quality standards and it is feasible for the learning process.